Hygienic Hand Disinfection in Nursing Practice in Context of Evidence Based Practice - Krause, Martin; Dolák, František (Vysoká škola polytechnická Jihlava, 2019)
Prevention and control of healthcare associated infections is very important for nursing care today. For the transmission of healthcare associated infections, contaminated hands of healthcare workers, including nurses, represent a very risky area. World Health Organization, Centers for Disease Control and Prevention, European Center for Disease Prevention and Control and other national and international institutions emphasize compliance of standard precautions according to Evidence Based Practice. A very effective method of prevention of healthcare associated infections is an implementation of the hygienic hand disinfection. It is the most accessible, easiest and economically inexpensive approach. An important aspect for the hygienic hand disinfection is an observance of five basic indications, technique and education not only of nurses. The review article summarizes current recommendations in implementation of the hygienic hand disinfection in providing nursing care according to Evidence Based Practice. Relevant information has been obtained through a qualitative review by review and synthesis method. The analysis is made from sources for the period 2015–2019. The acquired knowledges refers to important aspects of the hygienic hand disinfection.
Hygienická dezinfekce rukou v ošetřovatelské praxi v kontextu praxe založené na důkazech
Keywords: Evidence Based Practice; hygienic hand disinfection; healthcare associated infections; nursing; prevention; Evidence Based Practice, hygienická dezinfekce rukou, infekce spojené se zdravotní péčí, ošetřovatelství, prevence